A Note on Yield Variance and Mix Variance - Peles, Yoram C. (The Accounting Review, 1986)
[The sales activity variance as well as the corresponding production variance are typically partitioned into a yield variance and a mix variance. These latter variances have a defect which can lead to dysfunctional decisions. Since these variances are based on an average unit price which varies with respect to the unit of measurement selected, the same real events can appear as positive or negative variances. Alternative variances for mix and yield which do not have the above defect are suggested, based on expressing the units of goods sold by their cost of production.]